Evaluation of the lncRNA-miRNA-mRNA ceRNA network in lungs of miR-147 −/− mice - Zhang, Nan; Song, Gui-Yuan; Yu, Qing-Hua; Fan, Xin-Ming; Zhang, Wen-Shuo; Hu, Yong-Jian; Chao, Tian-Zhu; Wu, Yao-Yao; Duan, Shu-Yan; Wang, Fei; Du, Rui-Peng; Xu, Ping (Frontiers in Pharmacology, 2024)
Background: Previous studies have documented important roles for microRNA-147 (miR-147) in inflammation, radiation-induced injury, cancer, and a range of other diseases. Murine lungs exhibit high levels of miRNA, mRNA, and lncRNA expression.However, very little research to date has focused on the lncRNA-miRNA-mRNA competing endogenous RNA (ceRNA) networks associated with miR-147, and the regulation of lncRNAs and miRNAs in this setting remains poorly understood.Methods: After establishing a miR-147 -/-model mouse, samples of lung tissue were harvested for RNA-sequencing, and differentially expressed lncRNAs, miRNAs, and mRNAs were identified. The miRNA targets of these lncRNAs and the identified miRNAs were first overlapped to facilitate the prediction of target mRNAs, with analyses then examining the overlap between these targets and mRNAs that were differentially expressed. Then, these target mRNAs were subjected to pathway enrichment analyses. These results were ultimately used to establish a miR-147-related ceRNA network.Results: Relative to wild-type mice, the lungs of miR-147 -/-mice exhibited 91, 43, and 71 significantly upregulated lncRNAs, miRNAs, and mRNAs, respectively, together with 114, 31, and 156 that were significantly downregulated. The lncRNA-miRNA-mRNA network established based on these results led to the identification of Kcnh6 as a differentially expressed hub gene candidate and enabled the identification of a range of regulatory relationships. KEGG pathway enrichment showed that the mRNA targets of differentially expressed lncRNAs and miRNAs in the mice were associated with tumor-related signaling, endometrial cancer, bladder cancer, and ErbB signaling.Conclusions: These results suggest that the identified ceRNA network in miR-147 -/- mice shapes tumor-associated signaling activity, with miR-147 potentially regulating various lncRNAs and miRNAs through Kcnh6, ultimately influencing tumorigenesis.Future studies of the lncRNA, miRNA, and mRNA regulatory targets shown to be associated with miR-147 in the present study may ultimately lead to the identification of novel clinically relevant targets through which miR-147 shapes the pathogenesis of cancer and other diseases.